Olfaction and gustation abilities after a total laryngectomy - Mumović, Gordana (Radiology and oncology (Ljubljana), 2014)
Background A laryngectomy affects many of a patient's functions. Besides speech and respiratory-tract problems, olfaction and gustation problems can also have an influence on the quality of life. The aim of this study was to find out how often various nasal problems and decreased gustation appear after a laryngectomy. Patients and methods. One hundred and five laryngectomized patients (9 women, 96 men, aged 45-88 years), treated in two tertiary centers, were included in the study. They completed a questionnaire about various nasal problems, olfactory and gustatory capabilities, possible allergies and irritants in their environment, and the impact of the nasal and gustation problems on their quality of life. Results Olfaction was impaired in 51.4%, and was even not possible in 30.5%, of patients. Decreased gustation abilities were reported in 26.7%, and dysgeusia in 11.4%, of patients. Almost 21% of patients were bothered by an impaired gustatory ability and 50.5% of patients were affected by their loss of olfaction. Frequent nasal discharge was reported in 20%, frequent sneezing in 58.1%, and nasal itching in 33.3% of the laryngectomized patients. There were no correlations between the age and the olfaction and gustation abilities and between the allergy and the nasal symptoms, whereas the correlation between olfaction and gustation appeared significant (p=0.025). Conclusions Various nasal and gustatory problems were reported in more than 80% of laryngectomized patients. The olfaction and gustation abilities are connected and have a substantial impact on the quality of life. Like in the case of speech, the rehabilitation of olfaction is also necessary in all laryngectomized patients and must take place soon after the completion of the treatment.
Keywords: gustation; laringektomija; laryngectomy; okus; olfaction; quality of life; questionnaire; voh